The impact of SARS‐CoV‐2 in dementia across Latin America: A call for an urgent regional plan and coordinated response. Issue 1 (23rd November 2020) - Ibanez, Agustin; Santamaria‐Garcia, Hernando; Guerrero Barragan, Alejandra; Kornhuber, Alexander; Ton, Alyne Mendonca Marques; Slachevsky, Andrea; Teixeira, Antonio Lucio; Mar Meza, Beatriz Marcela; Serrano, Cecilia M.; Cano, Carlos; Arias Gonzalez, Carolina; Gonzalez‐Billault, Christian; et al.
Abstract: The SARS‐CoV‐2 global pandemic will disproportionately impact countries with weak economies and vulnerable populations including people with dementia. Latin American and Caribbean countries (LACs) are burdened with unstable economic development, fragile health systems, massive economic disparities, and a high prevalence of dementia. Here, we underscore the selective impact of SARS‐CoV‐2 on dementia among LACs, the specific strain on health systems devoted to dementia, and the subsequent effect of increasing inequalities among those with dementia in the region. Implementation of best practices for mitigation and containment faces particularly steep challenges in LACs. Based upon our consideration of these issues, we urgently call for a coordinated action plan, including the development of inexpensive mass testing and multilevel regional coordination for dementia care and related actions. Brain health diplomacy should lead to a shared and escalated response across the region, coordinating leadership, and triangulation between governments and international multilateral networks.